2020
DOI: 10.7498/aps.69.20191995
|View full text |Cite
|
Sign up to set email alerts
|

Generation of ultra-fast pulse based on bismuth saturable absorber

Abstract: We demonstrate a bismuth (Bi) saturable absorber (SA) for generating ultrafast pulse. The Bi SA is fabricated by the Bi film deposited on the surface of microfibers through using magnetron sputtering. Its nonlinear optical properties are investigated. The as-prepared Bi SA has outstanding nonlinear absorption property demonstrated by the open aperture (OA) <i>Z</i>-scan system at 1500 nm and balanced twin-detector method at 1560 nm. The nonlinear optical property of Bi SA shows that the modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…At present, there are two main fabrication methods, one is called the topdown method, and the other is called the bottom-up method [49][50][51]. The former includes mechanical exfoliation (ME) [52][53][54], liquid phase exfoliation (LPE) [27,43,55], electrochemical exfoliation [51,56], thermal annealing [57], plasma thinning [58,59] and sonochemical exfoliation method [60][61][62][63]; the latter includes chemical vapor deposition (CVD), pulsed laser deposition [64][65][66][67], hydrothermal method [66], van der Waals epitaxy [68,69] and magnetron sputtering deposition (MSD) [48,70]. We will briefly introduce three common preparation methods: ME, LPE and CVD.…”
Section: Fabrication Methods Of Black Phosphorus and Its Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are two main fabrication methods, one is called the topdown method, and the other is called the bottom-up method [49][50][51]. The former includes mechanical exfoliation (ME) [52][53][54], liquid phase exfoliation (LPE) [27,43,55], electrochemical exfoliation [51,56], thermal annealing [57], plasma thinning [58,59] and sonochemical exfoliation method [60][61][62][63]; the latter includes chemical vapor deposition (CVD), pulsed laser deposition [64][65][66][67], hydrothermal method [66], van der Waals epitaxy [68,69] and magnetron sputtering deposition (MSD) [48,70]. We will briefly introduce three common preparation methods: ME, LPE and CVD.…”
Section: Fabrication Methods Of Black Phosphorus and Its Analogsmentioning
confidence: 99%
“…Bulk bismuth is metallic and diamond-shaped in natural state. Studies have shown that when the number of layers is reduced to below 22, bismuth will show the property of topological insulator; when the number of layers is less than 8, it will show the quantum spin Hall phase, and in the case of single layer Bi shows the property of semiconductor [70]. There are many allotropes of Bi such as α-Bi and β-Bi, etc.…”
Section: Bismuthenementioning
confidence: 99%